Shape memory polytriazole elastomers from aromatic monomers: Synthesis and properties. (December 2018) - Ragin Ramdas, M.; Vijayalakshmi, K.P.; Munirathnamma, L.M.; Ravikumar, H.B.; Santhosh Kumar, K.S.
Graphical abstract: Abstract: In this contribution, a shape memory elastomer is synthesized from aromatic monomers by using copper catalyzed azide-alkyne polycycloaddition reaction (CuAAC). An aromatic trifunctional azide (M1) on click reaction with an aromatic trifunctional propargyl monomer (phloroglucinol based, M3) resulted in the formation of elastomeric shape memory polymer (E-SMP) with trigger temperature (Ttrig ) of 35 °C. Interestingly, a bifunctional monomer (propargyl quinol, M2) on click cross-linking with M1 led to a polytriazole thermoset ( NE-SMP) with Ttrig of 92 °C. Both E-SMP and NE-SMP possess gel content > 97%. The unprecedented formation of E-SMP is attributed to its high free volume as experimentally evidenced from PALS study. In computational modeling, it is evidenced that the triazole units in each phenyl ring are interacting to one another to create vacant spaces in the cross-linked polymer. The pore diameter is about 1 nm in E-SMP and 0.5 nm in NE-SMP. The triazole units undergo H-bonding with each other which facilitate the folding of polymer chains (and pores). The E-SMP exhibited fast shape recovery (12 s) whereas NE-SMP required 40 s. The E-SMP is thermally stable up to 260 °C (T 5% ).